Inside Cover: Catalytic Decomposition of N2O over Co–Ti Oxide Catalysts: Interaction between Co and Ti Oxide (ChemCatChem 12/2016). Issue 12 (21st June 2016) - Zhang, Chi; Zhang, Zhiping; Sui, Chao; Yuan, Fulong; Niu, Xiaoyu; Zhu, Yujun
Abstract : The Cover shows that N2 O from plant can be effectively decomposed into N2 and O2 over a series of Co‐Ti oxides. In their Full Paper, C. Zhang et al. show that deactivation occurred over time for the Co3 O4 catalyst, however, Co0.6 Ti maintained nearly 100 % N2 O conversion for at least 30 h. Moreover, the Co0.6 Ti catalyst showed much stronger resistance against 1.5 vol. % O2, 2.4 vol. % H2 O, or 1.6 vol. % NO in the feed compared with the Co3 O4 catalyst. The existence of a strong interaction between Co and Ti oxides in the Cox Ti catalysts is thought to be the reason, leading to a larger BET specific surface area and better structural stability than the Co3 O4 catalyst. The deactivation of the Co3 O4 catalyst is attributed to even weaker structural stability, leading to the decrease in the amount of surface Co 3+ . More information can be found in the Full Paper by C. Zhang et al. onpage 2155 in Issue 12, 2016 (DOI:10.1002/cctc.201600231 ).